PERFORMANCE EVALUATION OF HOMOGENEOUS CHARGE COMPRESSION IGNITION COMBUSTION ENGINE – A REVIEW - Kodancha, Pradyumna; Pai, Anand; Kini, Chandrakant R; Bayar, Rajesh K (Journal of Engineering and Technological Sciences, 2020)
The development of HCCI combustion technology has been drawing a great deal of attention from researchers. This survey explains ongoing research methodologies and results. HCCI combustion, other than conventional combustion, is purely based on chemical kinetics. At present the automobile sector faces the problem of emissions and needs to develop clean technologies. However, HCCI operation still has issues such as ignition control, combustion phasing control, operating range control, cold start, and UHC (unburned hydrocarbon) and CO (carbon monoxide) emissions. The challenge is to overcome these problems without compromising other engine parameters and performance. For HCCI, the mixture preparation is especially important, while the compression ratio, IVC (inlet valve closure) timing, inlet pressure, inlet temperature and EGR play a very prominent role in controlling it. This paper will go through a detailed discussion of all the above conditions.